Eco-Enzym Based on Household Organic Waste as Multi-Purpose Liquid - Adelliya Novianti; I Nengah Muliarta (Program Studi Magister Sains Pertanian Program Pascasarjana Universitas Warmadewa, 2021)
Waste is the residue of human daily activities or natural processes in the form of solid or semi-solid organic or inorganic substances that are biodegradable or non-biodegradable which are considered no longer useful and are disposed of into the environment. Sorting according to nature is divided into two types: organic and inorganic waste. In addition, the trash cans are also sorted based on the classification of household waste, commercial waste, building waste, and waste from public facilities. The literature review is carried out on the awareness that knowledge is constantly increasing (accumulating), that our research topic, society, and area of ​​research have been explored by people before, and that we can learn from what these people have done. So, we are not the first to research the topic, society, and area. Eco-enzyme was first developed by Dr. Rosukon Poompanvong, a founder of the Thai Organic Farming Association who has been researching since the 1980s. Eco-enzymes were introduced more widely by Dr. Joean Oon, a Naturopathy researcher from Penang, Malaysia. In the socialization material for the Nusantara Eco Enzyme Community (KEEN), 70% of the waste that is disposed of in Final Disposal Sites (TPA) is organic waste that causes unpleasant odors in the environment, reduces the level of plastic recycling, and poses the risk of explosions and decomposition of organic waste as well. produce methane gas. The advantages of this product are: it has antibacterial and antifungal activity, can release residual deposits on water pipes to prevent clogging of water pipes, can absorb pollutants caused by cigarette smoke, motor vehicle fumes, and the like, can release ozone during the fermentation process. , as well as eco enzyme residue that flows underground will be able to clean underground water, and most importantly, this product is very easy to make, the ingredients needed are also quite cheap so it is very practical to apply.